Design of Arduino Uno-Based Automatic Object Sorter Belt Conveyor System Using Ultrasonic Sensors - Restuasih, Sinta; Gamayel, Adhes; Agustino, Rano (Journal of Global Engineering Research and Science, 2022)
Belt conveyor is a fairly simple equipment used to transport load units or bulkmaterials with a large capacity, the tool consists of belts that are resistant tothe transport of solid objects. The sabuk used in this Belt Conveyor is madefrom various types of materials, for example from rubber, plastic, leather ormetal which depends on the type and nature of the material to be transported.The testing process of this tool starts by turning on the Conveyor Belt, therotation on the Conveyor Belt is constant at a speed of 3.1 m / min and thereis no speed setting, the speed of the Conveyor Belt can be known using theTachometer tool and can be calculated manually using the formula v = s / twhere v = speed, s = distance and t = time. When the object is attached to theConveyor Belt the object will run and pass through the Ultrasonic sensor,when the position of the object is directly under the sensor, the sensor willdetect the object based on the height or distance between the sensor and theobject, so that Arduino Uno can carry out the work process of the object fallsinto category A, B or C.